Parent-Focused Sexual Abuse Prevention: Results From a Cluster Randomized Trial. (February 2022) - Guastaferro, Kate; Felt, John M.; Font, Sarah A.; Connell, Christian M.; Miyamoto, Sheridan; Zadzora, Kathleen M.; Noll, Jennie G.
This study tested whether a child sexual abuse (CSA) prevention program, Smart Parents–Safe and Healthy Kids (SPSHK), could be implemented as an additional module in evidence-based parent training and whether the added module might detract from the efficacy of the original program. In a cluster randomized trial, six community-based organizations were randomized to deliver Parents as Teachers (PAT) with SPSHK (PAT+SPSHK) or PAT as usual (PAT-AU). CSA-related awareness and protective behaviors, as well as general parenting behaviors taught by PAT were assessed at baseline, post-PAT, post-SPSHK, and 1-month follow-up. Multilevel analyses revealed significant group by time interactions for both awareness and behaviors ( ps < .0001), indicating the PAT+SPSHK group had significantly greater awareness of CSA and used protective behaviors more often (which were maintained at follow-up) compared to the PAT-AU group. No differences were observed in general parenting behaviors taught by PAT suggesting adding SPHSK did not interfere with PAT efficacy as originally designed. Results indicate adding SPHSK to existing parent training can significantly enhance parents' awareness of and readiness to engage in protective behavioral strategies. Implementing SPHSK as a selective prevention strategy with at-risk parents receiving parent training through child welfare infrastructures is discussed.